FORMULASI PUPUK HAYATI SERBUK MENGGUNAKAN BAKTERI PELARUT FOSFAT INDIGENUS ASAL TANAH GAMBUT RIAU DALAM BERBAGAI BAHAN PEMBAWA - Dewi Haryanti; Delita Zul; Bernadeta Leni Fibriarti (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Peat soil has been known for its low content in phosphor (P). On the other hand, P solubilizing process is naturally slow. Inoculation of phosphate solubilizing bacteria (PSB) could increase this process. Therefore, the exploration of bacteria with such potential for use as biofertilizer agents is needed. Quality of biofertilizer depends on the viability and amount of bacteria contained, it is also influenced by type of carrier material. This research was aimed to find the appropriate carrier materials in production of biofertilizer which were contained PSB agent and to determine the quality of biofertilizer produced at a certain storage time. As many as 4 selected PSB isolates (BB_UB6, BB_K9, BB_K2, and BB_HS13) were used to produce 3 starter combinations. The starters were prepared by growing the isolates in Pikovskaya’s media. Biofertilizer was produced by inoculating each starter into the peat and wood charcoal as carrier material and was fermented for 4 days. Biofertilizer quality was determined by calculating the PSB cells number during 0, 30, 60, and 90 days storage time and the degree of biofertilizer acidity. The cell numbers of starter I, II, and III ranged from 8.2.1010-2.9.1011 CFU/g, 5.3.1010-2.9.1011 CFU/g, and 8.0.1010-2.9.1011 CFU/g, respectively in a period of storage 0-90 days. The highest cell number at the end of storage was found from biofertilizer produced by using peat, as carrier material which was kept at 40C (1,3.1011 CFU/g, starter I), (8.6.1010 CFU/g, starter II), and (9.6.1010 CFU/g, starter III). Biofertilizer acidity was relatively neutral, 6.38. Based on the results obtained, peat was revealed as a good carrier material and the quality of biofertilizers which were produced was still good.